Respuesta :

Obtuse: b^2 + c^2 > a^2

Right: b^2 + c^2 = a^2

Acute: b^2 + c^2 < a^2



A^2 + B^2 + c^2 - 2bc*cosA
As (A), is an Obtuse cos A is Negative say 2bccosA = - k then;
a^2 = b^2 + c^2 + k
a^2 > b^2 + c^2


So, your Answer would be (B)
Hope this helps!!.!

Obtuse: b^2 + c^2 > a^2

Right: b^2 + c^2 = a^2

Acute: b^2 + c^2 < a^2



A^2 + B^2 + c^2 - 2bc*cosA
As (A), is an Obtuse cos A is Negative say 2bccosA = - k then;
a^2 = b^2 + c^2 + k
a^2 > b^2 + c^2


So, your Answer would be (B)
Hope this helps!!.!

ACCESS MORE